29.9k views
5 votes
Solve for y.......

6 = 2(y + 2)


User Thuga
by
6.0k points

2 Answers

3 votes
Rewrite the equation as 2(y+2)=6

Divide each term in 2 (y+2)=6 by 2 and simplify

2(y+2)/2=6/2

Simplify the left side

Cancel the common factor of 2

x(y+3)x=6/2

Divide y+2 by 1

y+2=6/2

Simplify the right side

Divide 6 by 2

y+2=3

Move all terms not containing y to the right side of the equation

y=1
User WeinForce
by
5.1k points
7 votes


\qquad \qquad \bf \huge\star \: \: \large{ \underline{Answer} } \huge \: \: \star

  • y = 1


\textsf{ \underline{\underline{Steps to solve the problem} }:}


\qquad❖ \: \sf \:6 = 2(y + 2)


\qquad❖ \: \sf \:(y + 2) = \cfrac{6}{2}


\qquad❖ \: \sf \:y + 2 = 3


\qquad❖ \: \sf \:y = 3 - 2


\qquad❖ \: \sf \:y = 1


\qquad \large \sf {Conclusion} :

  • Value of y = 1
User Tomleb
by
5.4k points